BUSP: um protocolo adaptado para uma rede de monitoramento de dados utilizando transporte urbano - Cordeiro, Rafael (2021)
This dissertation presents a mobility model designed through the use of trace for the movement of public transport buses in the city of Curitiba-PR, in order to represent all urban public transport in the city. The built model offers conditions for assessing the capacity of the environment as a platform for the construction of a VDTN, as well as the improvement of routing protocols, in order to take advantage of the characteristics inherent to the scenario. The work also presents two proposals for forwarding messages tested with the mobility model, through modifications of the Spray and Wait protocol. The proposals, named BUSPv15 and BUSPv16, are based on a preclassification of public transport vehicles according to their logical proximity to the destination, in order to prioritize the transmission of messages to buses that have a better class. In order to reduce latency in the delivery of messages, the sending queue starts to be sorted prioritizing the most recently generated messages and therefore less likely to have already been delivered. In order to further reduce the overhead, BUSPv16 implements a technique in the transmitting node, deleting its copies of the message as soon as it is transmitted to a better class node. Then, the proposals were evaluated and compared to the classic protocols Epidemic, ProPHET and Spray and Wait through simulations performed in the simulator software The One, using the mobility model created from real scenario and a traffic model for monitoring applications. The results obtained are analyzed and interpreted with the aid of heat maps, demonstrating the feasibility of using the mobility of urban public transport vehicles in the city to transport information. The results also indicate that the BUSPv15 protocol presented the best delivery ratios, when compared to the other protocols, with latency and overload values below the Epidemic and ProPHET protocols. The results regarding the overload of the BUSPv16 protocol are the best among all protocols, demonstrating the gains of the proposed strategy, maintaining better values of delivery rate and latency than the classic protocols in most simulated scenarios.